In vivo protective effect of Copaifera langsdorffii hydroalcoholic extract on micronuclei induction by doxorubicin. Issue 8 (19th May 2012) - Alves, Jacqueline Morais; Munari, Carla Carolina; de, Moacir; Furtado, Ricardo Andrade; Senedese, Juliana Marques; Bastos, Jairo Kenupp; Tavares, Denise Crispim
ABSTRACT Copaifera lansdorffii Desf. is known as 'copaíba', 'copaiva' or 'paú‐de‐óleo', and is found in part of Brazil. The present study was undertaken to evaluate the genotoxic potential of C. langsdorffii leaf hydroalcoholic extract (CLE) and its influence on the genotoxicity induced by the chemotherapeutic agent doxorubicin (DXR) using the Swiss mouse peripheral blood micronucleus test. HPLC analysis of CLE using two monolithic columns linked in series allowed quantification of two major flavonoid heterosides, quercitrin and afzelin. Animals were treated with CLE by gavage at doses of 10, 20, 40 and 80 mg kg−1 body weight per day, each for 20 days. Peripheral blood samples were collected at 24 and 48 h, and 7, 15 and 21 days after the beginning of the treatment. For the antigenotoxicity evaluation, the animals treated with different concentrations of CLE received DXR (15 mg kg−1 body weight, intraperitoneal) at day 20. The peripheral blood samples were collected 24 and 48 h after the treatment with DXR. The results demonstrated that CLE itself was not genotoxic in the mouse micronucleus assay. In animals treated with CLE and DXR, the number of micronucleus was significantly decreased compared with animals receiving DXR alone. The putative antioxidant activity of one or more of the active compounds of CLE may explain the effect of this plant on DXR genotoxicity. Copyright © 2012 John Wiley & Sons, Ltd.